Data transfer over a low voltage power line for data acquisition and monitoring of electrical appliances - Khan, Sheroz; Omar, Jamaludin; Khalifa, Othman Omran; Islam, Md. Rafiqul; Adam, Ismail; Hassan, Abu Bakar (2006)
This article presents the design and implementation of a data communication system over a low voltage power line, meant primarily for applications of data acquisition from sites and monitoring of electrical appliances at the sites. The hardware developed, the interfacing required and the software used for implementation of the protocol are addressed. The developed system has been tested and results in a noise free and noisy power line system are reported. This paper reviews the previous studies on the power line as a transmission medium, proposes and evaluates the noble protocol for such applications.